Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10856-013-4863-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable and redox-responsive chitosan/poly(l-aspartic acid) submicron capsules for transmucosal delivery of proteins and peptides

Abstract: The development of peptides and proteins is hampered by their rapid clearance in liver and other body tissues by proteolytic enzymes, so these drugs are difficult to administer except for the injection. Here, we designed and fabricated a novel biodegradable and redox-responsive submicron capsules through the layer-by-layer technique with poly(L-aspartic acid) and chitosan for transmucosal delivery of proteins and peptides. TEM graphs reveal that the intact submicron capsules were obtained and the shell of subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Zheng et al designed and synthesized biodegradable redox-responsive nanocapsules adopting the layer-by-layer technique with poly (L-aspartic acid) and chitosan as vehicles for transmucosal delivery of proteins and peptides [51]. TEM images showed that intact nanocapsules were obtained and the shell of the nanocapsules was about 40 nm.…”
Section: Physiological Stimuli-triggered Deliverymentioning
confidence: 99%
“…Zheng et al designed and synthesized biodegradable redox-responsive nanocapsules adopting the layer-by-layer technique with poly (L-aspartic acid) and chitosan as vehicles for transmucosal delivery of proteins and peptides [51]. TEM images showed that intact nanocapsules were obtained and the shell of the nanocapsules was about 40 nm.…”
Section: Physiological Stimuli-triggered Deliverymentioning
confidence: 99%
“…Despite the intense study on capsule properties and their interaction with cells, there is a lack of reported data on how the capsules would behave if administered systemically in vivo. So far, there have been few reports on lbl capsules administered in vivo either via subcutaneous injection or nasal gavage [ 24 , 25 , 26 , 27 ]. There are attempts for MRI imaging of iron oxide modified capsules.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neither the thiol content nor the redox state of the thiol groups was controlled. The synthesis of thiolated PASP through carbodiimide mediated reactions is expensive and requires a large excess of the carbodiimide mediator . Thus, we used a simple synthetic pathway to prepare thiolated PASP, developed earlier by Szilágyi and co‐workers .…”
Section: Introductionmentioning
confidence: 99%